Comparative Effects of Exergaming and Treadmill Training on Balance and Mobility in Patients with Chronic Stroke - Wahid, Sidra; Zahoor, Idrees Ahmed; Mehmood, Sajid; Rana, Arif Ali; Awan, Noman Ghaffar; Raza, Ali (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2021)
Stroke is the chief cause of death and disability in the world that led toward impaired balance and mobility. Treatments that provide feedback, increase practice with multiple repetitions, and motivate patients are essential for rehabilitation after stroke. Objective: To determine whether playing video gaming exercises or treadmill training is better for balance and mobility post-stroke. Methods: A total of sixteen chronic stroke patients were randomly allocated to either the gaming or control groups. In this group patients were given visual feedback that was displayed on the screen. Participants played games for six weeks, work for 40 minutes per day, three days per week the therapy consisted solely of standing-up gameplay with no baseline therapy. The control group training with baseline treatment for six weeks, work for 40 minutes per day, three days per week. Both groups were tested earlier the study following intervention later 6 weeks. The Berg Balance Scale and TUG were used as outcome measures (Timed Up and Go test). Results: No statistically significant difference was found between the groups when analyzed post-treatment, but some significant differences were found within the group. By assuming equal variances and degree of freedom 14, there was no statistically significant difference, the p-value for BBS before VR was .170, and after VR was.686. However, the p-value for BBS before TT was .830, and after TT was .731. For TUG p-value before VR was .264 and after VR was .571. the p-Value for TUG before TT was .908 and after .416. The difference of mean for BBS before VR was .250 and after VR was 1.250 compared before TT 1.00000 and after 2.2500. For TUG, before VR was -1.000 and after VR was -2.250 comparing TUG pre-TT was -.62500 and post TT was -.3750. Conclusion: Although there was no statistical distinction between the two categories, the gamers were more excited and driven to be involved in the intervention for a longer period of time. Before considerable gains in commercially available general-purpose games may be realized, therapist guidance in developing more optimal movement choices may be required.